Pregnancy loss and risk of later dementia: A nationwide cohort study, Denmark, 1977–2017. Issue 1 (30th April 2019) - Basit, Saima; Wohlfahrt, Jan; Boyd, Heather A.
Abstract: Introduction: Pregnancy losses may be associated with increased risks of dementia. Methods: We conducted a register‐based cohort study in 1, 243, 957 women with ≥1 pregnancy in Denmark in the period 1977–2015. Using Cox regression, we estimated hazard ratios (HRs) comparing risks of dementia in women with and without pregnancy losses. Results: During 21, 672, 433 person‐years of follow‐up, 261, 279 women experienced a pregnancy loss, and 2188 women were diagnosed with dementia. Stillbirth was associated with an 86% increased risk of dementia overall (HR 1.86, 95% confidence interval [CI] 1.28–2.71). By contrast, miscarriage was not associated with later risk of dementia overall (single miscarriage, HR 0.99, 95% CI 0.87–1.12; recurrent miscarriages, HR 1.06, 95% CI 0.84–1.35). Adjustment for cardiovascular disease, hypertension, and diabetes did not meaningfully alter the association magnitudes. Discussion: Stillbirth and dementia may share underlying mechanisms, suggesting that a history of stillbirth should be considered when assessing dementia risk in women.